2019
DOI: 10.1186/s12907-018-0081-4
|View full text |Cite
|
Sign up to set email alerts
|

HER2 overexpression and correlation with other significant clinicopathologic parameters in Ivorian breast cancer women

Abstract: BackgroundThe overexpression of HER2 is associated with worse prognosis of breast cancer which responds favourably to anti-HER2 therapy. The objective of this study was to determine the frequency of HER2 and its association with clinicopathologic factors in breast cancer in Ivory Coast.MethodsThe study included 608 patients who were histologically diagnosed with invasive primary breast carcinoma. The immunohistochemistry testing for ER, PR, and HER2 was performed on the formalin fixed paraffin-embedded blocks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 44 publications
3
12
0
Order By: Relevance
“…The quantitated HER2 levels in FFPE samples allows us to investigate its correlation with other clinicopathologic factors including age, histological grade by Nottingham grading system, tumor size and metastasis status. HER2 levels were found to be associated significantly with histological grade based on Nottingham grading system using Spearman’s rank correlation analysis (ρ = 0.195, p = 0.001), a conclusion consistent with previous studies based on IHC analysis 19 , 20 . In the same study, we found that age was negatively associated with HER2 with statistical significance based on IHC analysis (ρ = − 0.117, p < 0.05), but not based on the absolutely quantitated HER2 levels (ρ = − 0.084, p = 0.127) (Supplementary Table 2 ).…”
Section: Resultssupporting
confidence: 89%
“…The quantitated HER2 levels in FFPE samples allows us to investigate its correlation with other clinicopathologic factors including age, histological grade by Nottingham grading system, tumor size and metastasis status. HER2 levels were found to be associated significantly with histological grade based on Nottingham grading system using Spearman’s rank correlation analysis (ρ = 0.195, p = 0.001), a conclusion consistent with previous studies based on IHC analysis 19 , 20 . In the same study, we found that age was negatively associated with HER2 with statistical significance based on IHC analysis (ρ = − 0.117, p < 0.05), but not based on the absolutely quantitated HER2 levels (ρ = − 0.084, p = 0.127) (Supplementary Table 2 ).…”
Section: Resultssupporting
confidence: 89%
“…HER2 positive is related to a greater mitotic index, which is one of the components of the Nottingham grade that indicates the severity of BC (29,30) . The overexpression of HER2, the high tumor grade, and the young age of our study population were unfavourable clinicopathologic factors, which are in accordance with the literature data of some studies (31,32) . In contrast, these patients should receive anti-HER2 targeted therapy and chemotherapy, which likely improve their survival.…”
Section: Discussionsupporting
confidence: 90%
“…The overexpression of HER2 is a poor prognostic factor associated with inadequate differentiation, high cell proliferation, metastasis to lymph nodes, and often resistance to specific chemotherapy. HER2 overexpression is also associated with a higher risk of recurrence compared with that in HER2-negative mammary tumor [30]. The HER group plays an important role in the signaling pathway controlling cell growth and differentiation.…”
Section: Discussionmentioning
confidence: 99%